Association of malnutrition with SARS-CoV-2 vaccine response in patients undergoing hemodialysis. Issue 12 (December 2022) - Lin, Ting-Yun; Hung, Nai-Kuan; Hung, Szu-Chun
Summary: Background & aims: Patients undergoing dialysis are less likely to develop immune responses to SARS-CoV-2 vaccine. Malnutrition is common in the dialysis population. However, whether malnutrition contributes to the impaired immunogenicity remains unknown. The aim of this study was to assess the association between nutritional status and SARS-CoV-2 vaccine response in patients receiving maintenance hemodialysis. Methods: A total of 206 hemodialysis patients (mean age, 67 ± 13 years) without prior SARS-CoV-2 infection were examined for the primary outcome of seroconversion, defined as the detection of IgG antibodies (≥50 AU/mL) to the receptor-binding domain of the S1 spike protein of SARS-CoV-2 one month after a priming dose of ChAdOx1 nCoV-19, an adenovirus-vectored vaccine. Nutritional status was assessed by using the Controlling Nutritional Status (CONUT) score, an objective indicator of nutrition incorporating serum albumin, total cholesterol, and total lymphocyte count, as well as the subjective global assessment (SGA). Results: Overall, 16.5% of patients were classified as malnourished, and 64.1% of patients were at risk for malnutrition based on the CONUT score. Anti-SARS-CoV-2 IgG were the highest in patients with normal nutrition. In multivariate logistic regression analyses adjusted for age, sex, comorbidities, and use of immunosuppressants, patients with malnutrition remained less likely to develop an antibody response than those with normal nutrition (odds ratio 0.23, 95% CI, 0.07–0.76). SGA was a significant predictor of anti-SARS-CoV-2 IgG seroconversion in univariate but not multivariate analyses. Conclusions: Malnutrition according to CONUT score is associated with impaired humoral responses to SARS-CoV-2 vaccination in patients undergoing hemodialysis. Our results highlight the importance of incorporating nutritional assessment into routine dialysis care to identify patients at risk for suboptimal immune responses after SARS-CoV-2 vaccination. Further research is needed to determine whether nutritional intervention can improve immune responses in these vulnerable patients.